Integration of Islamic Values in Achieving the Sustainable Development Goals (SDGs) through Islamic Religious Education - Rita Anisaturrizqi; Muhammad Akhyar Aji Saputra (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: This study is grounded in the importance of incorporating spiritual and moral perspectives to support the achievement of the Sustainable Development Goals (SDGs) through Islamic religious education. Objective: This study aims to identify the conceptual and practical contributions of Islamic religious education to the implementation of the SDGs across various aspects of social life. Method: The study employs a descriptive qualitative approach, drawing on a literature review of academic sources, global policy documents, and relevant Islamic teachings. Result: The findings indicate that Islamic values, such as social justice, environmental stewardship, education for all, and social responsibility toward vulnerable groups, are highly aligned with the SDGs, particularly Goal 4 (Quality Education), Goal 10 (Reduced Inequalities), and Goal 16 (Peace, Justice, and Strong Institutions). Conclusion: The study concludes that Islamic religious education can serve as an ethical and spiritual foundation for sustainable development practices that extend beyond economic growth to encompass character formation, social awareness, and harmonious human coexistence. Contribution: This study contributes to the growing body of literature on the intersection of Islamic religious education and sustainable development by demonstrating the compatibility between Islamic values and the Sustainable Development Goals (SDGs).